Current perspectives on Farh's disease: a glimpse from the internal medicine unit - Gómez-Piña, Juan José; Luna, Vanessa Castro; Chávez, Alan David Arroyo; Valdés, Nallely Puebla; Alfaro, Natalia León; Trenado, Juan Carlos Arguello; Elicea, Mario Soria; García, Luis Rodrigo Bañuelos (International Journal of Research in Medical Sciences, 2025)
Background: Fahr's disease involves abnormal calcium deposits (calcium carbonate/phosphate) in the basal ganglia and other brain regions, primarily due to metabolic dysfunction, with rare autosomal dominant cases. These calcifications affect basal ganglia, thalamus, hippocampus, dentate nucleus, cerebral cortex, and subcortical white matter of the cerebellum. The aim of this study was to determine the prevalence of fahr's disease unrelated to secondary metabolic disorders (2017-2024). Methods: We conducted a retrospective review of hospital records between 2017 and 2024 to identify patients with a clinical diagnosis of Fahr's disease or those presenting with neurological abnormalities such as seizures, altered mental status, involuntary movements, or intracranial calcifications detected during diagnostic evaluations. Inclusion criteria required cranial CT scans to systematically assess calcifications in predefined brain regions: basal ganglia, thalamus, hippocampus, dentate nucleus, cerebral cortex, or subcortical cerebellar white matter. Results: Of 134 suspected Fahr’s disease cases, only 8 were confirmed on tomography, not clinically with a prevalence of 0.06%. None showed clinical basal ganglia involvement, but CT revealed calcifications: 2 in basal ganglia, thalamus, hippocampus, and cerebellum; 4 in basal ganglia, thalamus, and hippocampus; and 2 in basal ganglia and cerebral cortex. Conclusions: In our setting, Fahr's disease is generally underdiagnosed and is typically found incidentally through cranial CT scans. Its prevalence could potentially be even higher. Since most of these patients are asymptomatic, comprehensive extension studies are often not conducted for their evaluation. As a result, the current prevalence remains extremely low compared to other studies (around 1%).